Endotracheal Surfactant Combined With Budesonide for Neonatal ARDS - Deliloglu, Burak; Tuzun, Funda; Cengiz, Merve Meryem; Ozkan, Hasan; Duman, Nuray (Frontiers in Pediatrics, 2020)
Acute respiratory distress syndrome (ARDS) is a clinical condition characterized by acute diffuse inflammatory lung injury and severe hypoxemia. In 2017, the Montreux Consensus defined diagnostic criteria for ARDS in the neonatal period. The management of ARDS includes strict adherence to lung-protective ventilation strategies and therapeutic agents to improve gas exchange. We report two similar cases of premature infants with gestational ages of 23 and 24 weeks diagnosed with neonatal ARDS according to the Montreux definition. These patients developed acute worsening of oxygenation on the 30th and 28th day of life, respectively, while they were ventilated on volume-guarantee assist/control mode. Chest X-rays revealed bilateral diffuse opacity, there were no cardiogenic origins for pulmonary edema, and their oxygenation indexes were >8. Both cases fulfilled the neonatal ARDS criteria and the patients’ clinical conditions were associated with late onset neonatal sepsis. After lung recruitment maneuver, the infants began HFO volume-guarantee ventilation and received surfactant treatment. Since they showed a poor short-term response, intratracheal surfactant of 100 mg/kg plus budesonide of 0.25 mg/kg were administered and their oxygenation indexes were reduced stepwise. Both patients survived and were discharged home with spontaneous breathing of room air. Neonatal ARDS is generally an underdiagnosed condition associated with sepsis, pneumonia, and meconium aspiration. Impaired surfactant activity and reduced lung compliance play important roles in its pathophysiology. To our knowledge, this is the first case report indicating the possible therapeutic role of budesonide plus surfactant in ARDS treatment. Since ARDS is an entity not recognized in newborns, we want to emphasize neonatal ARDS diagnosis and underline that the combination of budesonide and surfactant may be a novel therapeutic option in the treatment of ARDS.